Uso de juegos Web para apoyar la enseñanza de las operaciones aritméticas básicas en el subnivel elemental de la Unidad Educativa Particular Ateneo durante el año lectivo 2023-2024 - Aucapiña Guerrero, Lester Michael (2024)
The incorporation of web games in education is an innovative strategy that seeks to enhance learning through interactivity, therefore this research seeks to analyze the use of web games of basic arithmetic operations by teachers in the elementary sub-level of general basic education in the Ateneo Private Educative Unit during the academic year 2023 – 2024. The methodology applied was based on the quantitative approach, with deductive method, exploratory - descriptive scope, whose research instrument was structured and adapted from the Curriculum of the Ministry regarding Elementary General Basic Education, applied through the survey technique to a sample of ten teachers of General Basic Education, where nine web games of basic arithmetic operations for the elementary sub-level of general basic education were characterized, taking the information from the Web Portal of Digital Educational Resources of the Ministry of Education of Ecuador taking into account the topics and skills with performance criteria of the elementary sub-level of general basic education. In the same way, the use of web games of basic arithmetic operations by teachers of the elementary sublevel of general basic education in the Ateneo Private Educational Unit was diagnosed, where for the second grade there is the topic of addition and subtraction titled "The Ogre Game" while in the third grade there is the topic of multiplication tables called "Multiplication Tables" in the fourth grade the topic of the notion of division called "Basic Division" is approached. Finally, it was possible to analyze the use of web games of basic arithmetic operations by teachers, the most used being "The addition and subtraction race" for third grade and the least used is "Quiz contest" which corresponds to second grade. Keywords: Web games, Teaching, Arithmetic Operations, Elementary Sublevel.